Financial investment strategies – Conceptual Framework - هاشم صبيحة قاسم; عبد الكريم يسرى عامر (Journal of Economics and Administrative Sciences, 2016)
The investor needs to a clear strategy for the purpose of access to the financial market, that is, has a plan to increase The share of the profits thinking entrepreneur and new, and highlights the importance of this in that it sets for the investor when it goes to the market, and when it comes out of it, and at what price to buy or sell the stock, and what is the the amount of money it starts. Fortunately, he does not need to invent his own investment strategy, because over the years the development of effective methods of buying and selling, and once you understand how to work these methods investor can choose the most appropriate methods and adapted image that fit his style investment . Here we note that the presence of a specific investment strategy exempt investors from sudden losses like any field of life, which is no doubt that the strategies adopted by the investor will affect the choice of type of securities that it intends to invest in it, leading to investors’ preferences varied and thus contrast the behavior of investors and the desired goal of investment . Therefore , the goal of current research is to review a variety of investment strategies that guarantee for the investor the right investment decision when the financial market being efficient or inefficient. In the event that the financial market prefers to efficiently build investor’s portfolio in light of considerations relating to diversification, risk , tax and liquidity and the timing of the investment, but if the financial market is efficient in front of the investor to follow a set of strategies based on several methods to evaluate securities .